Antifungal Activity of Citronella Oil Against Clinical Isolate Candida albicans - Misrahanum, Misrahanum; Nurfani, Adelia; Helwati, Hira (PHARMACY: Jurnal Farmasi Indonesia (Pharmaceutical Journal of Indonesia), 2022)
Citronella (Cymbopogon nardus (L.) Rendle) is commonly claimed as a multifunction plant. Citronella produces an essential oil whose quality standard was set in SNI 06-3953-1995. Citronella oil is used for traditional medication, such as an antimicrobial, antipyretic, analgesic, and many other functions. This study evaluated the in-vitro antifungal activity of citronella oil obtained from the farm in Menderek, Pintu Rime Gayo, Bener Meriah, Aceh, against clinical isolates of Candida albicans. The citronella oil analyzed using chromatography-mass spectrometry (GC-MS) showed chemical components of citronellal (26.06%), Î²-citronellol (26.314%), and geraniol (17.90%). Antifungal activity test of citronella oil against Candida albicans by well diffusion method showed the highest activity at 40% v/v concentration with the diameter of inhibition zone of 23.31Â±0.04 mm. The result of this study indicated that the citronella oil has a good potential to inhibit clinical isolate Candida albicans growth.